1994
DOI: 10.1172/jci117086
|View full text |Cite
|
Sign up to set email alerts
|

Keratinocyte growth factor is a growth factor for type II pneumocytes in vivo.

Abstract: Clin. Invest. 1994.93:1298-1306

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
239
4
1

Year Published

1995
1995
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 337 publications
(266 citation statements)
references
References 14 publications
(4 reference statements)
22
239
4
1
Order By: Relevance
“…In the present experiments, the same recombinant VEGF at the same concentrations failed to induce any increase in thymidine or BrdU incorporation in isolated type II cells, which, by contrast, responded strongly to KGF, consistent with previous findings in adult (26,35) as well as fetal (7) type II cells. Our findings, therefore, suggest that the proliferative effects of VEGF previously observed in lung explants were indirect.…”
Section: Discussionsupporting
confidence: 93%
“…In the present experiments, the same recombinant VEGF at the same concentrations failed to induce any increase in thymidine or BrdU incorporation in isolated type II cells, which, by contrast, responded strongly to KGF, consistent with previous findings in adult (26,35) as well as fetal (7) type II cells. Our findings, therefore, suggest that the proliferative effects of VEGF previously observed in lung explants were indirect.…”
Section: Discussionsupporting
confidence: 93%
“…However, other experimental approaches will be required to fully define the precise nature of KGF involvement in epithelial development. In this regard, earlier cell and organ culture studies have demonstrated that KGF is a paracrine mitogen for epithelial cells from a variety of different sources (Aaronson et al, 1991;Marchese et al, 1990;Pierce et al, 1994;Rubin et al, 1989;Ulich et al, 1994), as well as a morphogen in the ductal branching morphogenesis of the neonatal mouse seminal vesicle (Alarid et al, 1994) and the neonatal rat prostate (Sugimura et al, 1993). The extension of similar studies to other organ systems will provide a powerful approach in further elucidating the multiple roles of KGF during development.…”
Section: Discussionmentioning
confidence: 99%
“…In the alveolar epithelium, this progenitor cell-like function has been ascribed to AEC2 (13,31,36). AEC2 proliferate during embryonic and fetal life but, in the adult lung, in the absence of injury, are highly differentiated and do not normally divide (9,37). However, in response to environmental insult, some AEC2 become both hypertrophic and hyperplastic, such that cells undergo phenotypic and functional changes (17,24).…”
mentioning
confidence: 99%